INTERMIDIALIDADE COMO FERRAMENTA PARA DECOLONIALIDADE: JULIETH MORALES NA GALERIA CLAUDIA ANDUJAR NO INHOTIM - Santana Gomes, Letícia; Muniz Soares Valério, Ana Cláudia (Revista (Entre Parênteses), 2025)
This study foregrounds the Claudia Andujar Gallery at Instituto Inhotim, emphasizing the intermedial relationships activated by the work of Colombian visual artist Julieth Morales, whose practice articulates a deep connection to the land from an Indigenous perspective. Drawing on Mignolo (2017) and Vergés (2020), we examine the gallery as a decolonial instrument; on the role of Julieth Morales as an active agent within that framework; and on the intersections between decoloniality and intermediality. Employing the theoretical lenses of Lars Elleström (2017) and Irina Rajewsky (2020), we analyze the media configurations present in Morales’s work and the ways they generate meanings that foster social impact and transformation.